Theological anthropology, 500 years after Martin Luther : Orthodox and Protestant perspectives - Chalamet, Christophe; Delikostantis, Konstantinos, 1948-; Getcha, Job, Archbishop; Parmentier, Élisabeth, 1961- (Studies in systematic theology (Leiden, Netherlands), 2021)
"Theological Anthropology, 500 years after Martin Luther gathers contributions on the theme of the human being and human existence from the perspectives of Orthodox and Protestant theology. These two traditions still have much to learn from each another, five hundred years after Martin Luther's Reformation. Taking Martin Luther's thought as a point of reference and presenting Orthodox perspectives in connection with and in contradistinction to it, this volume seeks to foster a dialogue on some of the key issues of theological anthropology, such as human freedom, sin, faith, the human as created in God's image and likeness, and the ultimate horizon of human existence. The present volume is one of the first attempts of this kind in contemporary ecumenical dialogue"--